Connective Expressions as Metadiscourse Markers of Writing Quality in Undergraduate Students’ Expository Writing - BOUDERSA, Nassira (Journal of Human Sciences, 2014)
This  article examines  third  year  students’  expository  writing  and  the  use  of  conjunctive  expressions (connectives) as  markers  of  good  quality  essays  which  is  measured  in  terms  of  conjunctive  expressions’  appropriate  use  and  density,  and  is  reflected  by  the  teachers’  assigned  scores  to  the  students’  essays.  The  expository  essays  were  analyzed  for  connectives’  use  by   adopting  Halliday  and  Hasan’s (1976) taxonomy of conjunctive  cohesion.  The  expository  essays  were  divided  into  two  groups,   highly  scored  essays (above 12) and  poorly  scored  essays (below10) to  test  the  correlation  between  the  use  of  connectives  and  the  quality  of  essays, reflected  by  marks.  The  results  show that  when students use  lot of  connective  expressions , the quality of   their  writing  will  not  be  good,  but  when  they  use  a  little of   connective  expressions,  the  quality of their  writing  will be  good.  Accordingly,  the  hypothesis  upon  which  the  research  is  based,  that  there  is  a  positive  relationship  between  connective  expressions’  use  in terms  of  frequency  and  appropriacy,  and  the  students’  writing  quality,  showed  negative  results  and  the  hypothesis  was  not,  thus,  confirmed.